Beginning EFL Teachers' Emotional Labor Strategies in the Chinese Context - Li, Hanxi; Liu, Honggang (Frontiers in Psychology, 2021)
Teachers’ emotional labor strategies have been explored in different cultural contexts. However, beginning English as a foreign language (EFL) teachers have received scant research attention. This study seeks to conceptualize emotional labor strategies among Chinese beginning EFL teachers and investigate their general profiles. The developed Beginning EFL Teachers’ Emotional Labor Strategy Scale was assessed among 484 Chinese beginning secondary school EFL teachers. A final 20-item scale was obtained after a series of reliability (e.g., item analysis, internal consistency, composite reliability) and validity tests (e.g., construct validity, convergent validity, discriminant validity). The confirmatory factor analysis results supported the four-dimensional structure of emotional labor strategies in the beginning EFL teacher sample, encompassing surface acting, deep acting, positive consonance, and negative consonance. In addition, participants reported high levels of positive consonance and deep acting, and low levels of surface acting and negative consonance. Possible reasons for this are discussed in reference to the EFL educational context in China. The findings provide insights into sustainable development for Chinese beginning secondary school EFL teachers.